A biomimetic structured bio-based flame retardant coating on flexible polyurethane foam with low smoke release and antibacterial ability. (January 2023) - Meng, Dan; Wang, Kaihao; Wang, Wenjia; Sun, Jun; Wang, Haiqiao; Gu, Xiaoyu; Zhang, Sheng
Abstract: Flexible polyurethane foam (FPUF) is widely used in our life, but it is inherent flammable. The demand for environmental-friendly multi-functional FPUF has been increasing rapidly in the last decade. In this work, a novel bio-based flame retardant coating was constructed by chemically reacting sodium alginate (OSA) and polydopamine (PDA) on the FPUF, followed by depositing nanorod-like β-FeOOH molecules through complexation reaction to form a biomimetic structure. The limiting oxygen index of the coated FPUF samples reached 25.5%. The peak heat release rate was reduced by 45.0%, and the smoke density of the coated sample was decreased by 69.1% compared to that of the control FPUF sample. It was proposed that the OSA-PDA-β-FeOOH decomposed during combustion to promote the formation of compact crosslinked char and released inert gases to dilute the combustible gases, and the β-FeOOH transferred to Fe2 O3 to settled the smoke particles reducing the smoke release. Furthermore, the coating with shark skin like structure endowed FPUF antibacterial ability because of its good superoleophobicity underwater. This work provided a novel strategy to construct a biomimetic multifunctional coating on the FPUF. Graphical abstract: Image 1 Highlights: A biobased coating was constructed on flexible polyurethane foam (FPUF). The coating with a biomimetic structure improved the flame retardancy of FPUF. The LOI of the coated FPUF reached 25% after washing and/or abrasion. The coating decreased the peak smoke density of FPUF by 68.5%. FPUF with superoleophobicity underwater showed antibacteria for cleaning application.